How does the Public Attitude Towards Advertising Controversial Products & Advertising Ethics? - Khairawati, Salihah; Murtadlo, Mu’tashim Billah (Universitas Muhammadiyah Yogyakarta, 2020)
The aim of this paper is to determine attitudes towards the advertistment of certain controversial products and the reasons for being offensive among Indonessian peoples in Yogyakarta. This research method was qualitative, achieved by analyzing the responses of informans by depth interview method. The results indicated that peoples refused advertistment openly broadcasted of certain controversial products, such contraception, underwear, alcohol, and others. For cigarette, there were two responses most of them received cigarette advertisment and the other disagree. Advertisment should obeyying advertisment ethics and goverment should regulating advertisment for controversial products, especially when the advertisment contradictory with religions, values and social norms in muslims countries. The implication of this research for those involved in marketing, it is important that they are aware of possible cultural and religion sensitivities when entering a market or undertaking a standardized mass-media campaign across a region. Limitation of this reserach were few informans, further research can be suggested to conduct future study by taking more respondent and using quantitative method.